The Impact of Covid-19 on The Profitability of Manufacturing Companies Listed on The Indonesia Stock Exchange (IDX) - Adri, Mutia Tasyah; Kurniawan, Agung Widhi; Anwar; Ramli, Anwar; Nurman (PT. Maju Malaqbi Makkarana, 2023)
This study aims to determine the impact of COVID-19 on the profitability of manufacturing companies listed on the Indonesia Stock Exchange. This sample was taken from manufacturing companies listed on the Indonesia Stock Exchange (IDX) which can be accessed via the website (www.idx.co.id), the research sample was selected using the purposive sampling method of 22 manufacturing companies listed on the Indonesian stock exchange for the 2019-2021 period. The type of data used in this research is quantitative data obtained from financial reports that have been audited and published by manufacturing companies listed on the 2019-2021 Indonesian Stock Exchange. Data collection is done by using Documentation technique. In this research, the data source used is secondary data. The analytical methods used in this study include: Using Descriptive Statistical Tests and Difference Tests (Paired Sample T-Test) The results of this study indicate that it is concluded that the COVID-19 pandemic has had a significant impact on the profitability of manufacturing companies listed on the Indonesia Stock Exchange. NPM, ROA, and ROE underwent significant changes after the pandemic, indicating a decrease or increase in the financial performance of these companies. These results indicate the need for companies to adapt their business strategy and financial management to face the challenges posed by the COVID-19 pandemic in order to ensure the continuity and profitability of the company in the future.